Resolving the conformational dynamics of ErbB growth factor receptor dimers - Pawar, Aiswarya B.; Sengupta, Durba (Journal of Structural Biology, 2019)
The combinatorial dimerization of the ErbB growth factor receptors (ErbB(1) - ErbB(4)) are critical for their function. Here, we have characterized the conformational dynamics of ErbB transmembrane homo-dimers and hetero-dimers by using a coarse-grain simulation framework. All dimers, except ErbB (4-4) and ErbB(1-4), exhibit at least two conformations. The reported NMR structures correspond to one of these conformations, representing the N-terminal active state in ErbB(1-1) (RH2), ErbB(2-2) (RH1) and ErbB(4-4) (RH) homo-dimers and the LH dimer in ErbB(3-3) homo-dimer, validating the computational approach. Further, we predict a right-handed ErbB(4) dimer conformer that warrants experimental testing. The five hetero-dimers that have not yet been experimentally resolved display prominent right-handed dimers associating by the SmXXXSm motif. Our results provide insights into the constitutive signaling of ErbB(4) after cleavage of the extracellular region. The presence of the inactive-like dimer conformers leading to symmetric kinase domains gives clues on the autoinhibition of the receptor dimers. The dimer states characterized here represent an important step towards understanding the combinatorial cross associations in the ErbB family.
Keywords: Martini coarse-grained simulations; Membrane protein structure; Transmembrane dimer